The Effect of Accountability and Transparency on Cooperative Financial Management of Sakra Warih Conventional Consumer Cooperative of Banyumas Regency - Inggrid Marisca Rubiyanty; Afiq Chamim Mubaroq; Ascaryan Rafinda (Politeknik Ganesha Medan, 2025)
The aim of this research is to examine the effect of accountability and transparency on financial management at the Sakra Warih PDAM Conventional Consumer Cooperative, Banyumas Regency. The research population was all members and administrators of the cooperative, using a snowball sampling technique, resulting in 51 respondents. Data analysis used the causality and explanatory method with a 5-point Likert scale questionnaire instrument. Meanwhile, hypothesis testing uses structural equation modeling PLS (SEM-PLS) analysis. The research results show that accountability has no effect on financial management. This is likely due to the principles and objectives of cooperatives, which prioritize non-financial aspects, such as the welfare and productivity of their members. Meanwhile, transparency is related to financial management. These results validate agency theory which states that cooperatives have an obligation to provide information to their members, this serves as a reference for decision making. This research has theoretical implications, namely validating the importance of agency problems that must be overcome and practical implications for cooperatives to always increase accountability, especially non-financial aspects and transparency, in order to maintain continuity and achieve cooperative goals.